A gait retraining system using augmented-reality to modify footprint parameters: Effects on lower-limb sagittal-plane kinematics. (3rd January 2018) - Bennour, Sami; Ulrich, Baptiste; Legrand, Thomas; Jolles, Brigitte M.; Favre, Julien
Abstract: Improving lower-limb flexion/extension angles during walking is important for the treatment of numerous pathologies. Currently, these gait retraining procedures are mostly qualitative, often based on visual assessment and oral instructions. This study aimed to propose an alternative method combining motion capture and display of target footprints on the floor. The second objectives were to determine the error in footprint modifications and the effects of footprint modifications on lower-limb flexion/extension angles. An augmented-reality system made of an optoelectronic motion capture device and video projectors displaying target footprints on the floor was designed. 10 young healthy subjects performed a series of 27 trials, consisting of increased and decreased amplitudes in stride length, step width and foot progression angle. 11 standard features were used to describe and compare lower-limb flexion/extension angles among footprint modifications. Subjects became accustomed to walk on target footprints in less than 10 min, with mean (± SD) precision of 0.020 ± 0.002 m in stride length, 0.022 ± 0.006 m in step width, and 2.7 ± 0.6° in progression angle. Modifying stride length had significant effects on 3/3 hip, 2/4 knee and 4/4 ankle features. Similarly, step width and progression angle modifications affected 2/3 and 1/3 hip, 2/4 and 1/4 knee as well as 3/4 and 2/4 ankle features, respectively. In conclusion, this study introduced an augmented-reality method allowing healthy subjects to modify their footprint parameters rapidly and precisely. Walking with modified footprints changed lower-limb sagittal-plane kinematics. Further research is needed to design rehabilitation protocols for specific pathologies.